(3hajGJ GdCYjGfs - (3GHf NdcGf , CMeO Hf eMeO Hf EHQGgje Hf CHj HcQ GdHQecj GdGQHdj, TeS GdOjf CHh GdYHGS,J (B681 (3g` s
(3ChdgG (B:s
(3GdCejQ GdeNJGQ YR Gdedc eMeO Hf CHj GdbGSe YHjO Gddg GdeYQha HGdeSHMi s
(3BNQgG (B:s
(3BNQg BNQ JQLeI GdMGce HCeQ Gddg s
(3GfXQ Qbe (B567 (3, Qbe (B865 (3, Qbe (B1307 (3JGQjNs
(3fSNI SGHYI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B220 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B59s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B327 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B561 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B474 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs